2008
DOI: 10.1103/physrevstab.11.060402
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 5.4 MV laser triggered gas switch for multimodule, multimegampere pulsed power drivers

Abstract: Laser triggered, megavolt, megampere gas switches are frequently utilized to synchronize multiple pulsed power driver modules for inertial-confinement fusion, isentropic compression, and radiation physics experiments. The device developed to synchronize the 36 modules of the refurbished Z accelerator at Sandia National Laboratories is a 5.4 MV, 700 kA, sulfur-hexafluoride (SF 6 ) filled, laser triggered gas switch. At this operating level, switch jitter is 5 ns, the prefire rate is less than 0.1%, the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 27 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…Over the last 5 years, the sintered Schwartzkopf material became unavailable in the USA, and it was replaced by Elkonite 3W3, or other sintered tungsten copper materials from different companies. The ZR group at Sandia National Laboratories [47] tested electrode materials from several manufactures and found that the electrode erosion is highly depended on the sintering process for otherwise identical materials with the same composition by weight. Two materials were identified as good replacements for high current spark gap electrodes: The Mi-Tech Metals CW70E (68% W, 32% Cu) material and the copper infiltrated tungsten material (90% W, 10% Cu) from ATI Wah Chang.…”
Section: Electrode Material Switch Debris/dust and Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 5 years, the sintered Schwartzkopf material became unavailable in the USA, and it was replaced by Elkonite 3W3, or other sintered tungsten copper materials from different companies. The ZR group at Sandia National Laboratories [47] tested electrode materials from several manufactures and found that the electrode erosion is highly depended on the sintering process for otherwise identical materials with the same composition by weight. Two materials were identified as good replacements for high current spark gap electrodes: The Mi-Tech Metals CW70E (68% W, 32% Cu) material and the copper infiltrated tungsten material (90% W, 10% Cu) from ATI Wah Chang.…”
Section: Electrode Material Switch Debris/dust and Erosionmentioning
confidence: 99%
“…The extensive work on the ZR switches at Sandia National Laboratories [46][47][48] let to a redesign of the electrode configuration for the Electra laser triggered switches. It is believed that the switch gap should have a more uniform electric field along the switch axis.…”
Section: Flat Electrodesmentioning
confidence: 99%
“…According to a) Electronic mail: whhnjznl@yahoo.cn Ampère's law B 0 ¼ l 0 I 0 /l, we combine Eqs. (3) and (4) to obtain…”
Section: Mitl Flow Theory With Both Electrons and Ionsmentioning
confidence: 99%
“…[1][2][3][4][5] In the MITL, when electrons emit from cathode under the condition of the large electric field stresses over the electron-explosive-emission threshold, 6 ion emission from anode may occur with the very high pulse power and current density. 7 In the practical application, the phenomena of ion emission is particularly possible to emerge at the end of MITL near load, where anode surface heating mechanisms (such as Ohmic heating because of linear current convergence on the anode and electron deposition from the load) become significant.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations presented here extend a recently developed Monte Carlo model of electronegative gas breakdown and streamer propagation. 6 Here, the model is applied to the laser-triggered gas switches used on the Z pulsed-power facility at Sandia National Laboratories, 1,7 where SF 6 is used as the working gas in order to provide higher voltage switch operation. The goal is to develop 2D and 3D models capable of treating the switch performance through the successive stages of laser-initiation of one or more thin plasma filaments between the electrodes, the subsequent streamer/leader propagation that provides the initial current contact between the electrodes, and finally the formation of a high-current conduction channel.…”
Section: Introductionmentioning
confidence: 99%